Production of biodiesel from neem seed oil - Banik, SK; Rouf, MA; Rabeya, T; Khanam, M; Sajal, SI; Sabur, SB; Islam, MR (Bangladesh Journal of Scientific and Industrial Research, 2018)
Neem oil was extracted from neem seeds by mechanical extraction method. Yield of oil was 21.32%. The physicochemical properties of the extracted oil were studied in detail. The oil corresponds to diesel except acid value (14.21%) and sulphur content. Acid esterification was performed to reduce the acid value which was followed by transesterification to produce biodiesel. The conditions of the transesterification of the oil were optimized and were found to be 20% methanol and 1.0% NaOH at 60 ̊ C for 90 min. The optimum yield of biodiesel was 98 %. Finally, the performance study in a diesel engine was conducted with diesel and biodiesel blends. The brake thermal efficiency for 5% blend of biodiesel was 16.67% for brake power of 0.79 KW. Bangladesh J. Sci. Ind. Res.53(3), 211-218, 2018